THE URGENCY OF INSTILLING SA'O LOCAL WISDOM VALUES IN ENVIRONMENTAL CONSERVATION EFFORTS FOR STUDENTS IN NGADA REGENCY - Fransiskus Xaverius Rema; Nana Supriatna; Dadang Sundawa; Neiny Ratmaningsih (Prima Magistra: Jurnal Ilmiah Kependidikan, 2025)
The traditional architecture of Sa'o, which is the traditional house of Bajawa, demonstrates the preservation of environmental sustainability through local wisdom. This study aims to: (1) examine the values of local wisdom in the development and governance of Sa'o and the environment in Bena Village, and (2) analyze the role of this local wisdom as respect for nature and its relevance as an educational medium for students. The study concludes that the local wisdom of Bena Village is a valuable form of social and ecological capital. Therefore, a strategy is needed to help students understand, appreciate, and preserve these values so they can face global environmental challenges. The findings reveal that local wisdom in Sa'o enables students to maintain harmony in their lives through traditions and rituals that have been passed down for generations. This wisdom can also serve as a reference for knowledge and understanding to overcome and anticipate current local environmental issues, particularly those related to pollution.